Predictor of Inhospital Mortality Following Pci in High Risk Patients - Abdul Basit, Sumaira Fareed Khan, Shahbaz Ali Shaikh, Muhammad Iftikhar Alam, Romana Awan, Syed Kashif Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To identify predictors of in-hospital mortality in high-risk patients undergoing percutaneous coronary intervention at the Department of Cardiology, Tertiary care hospital Peshawar. Methodology: A retrospective observational study was conducted from January 2023 to June 2023. A total of 220 patients who underwent high-risk PCI were included using consecutive sampling. Data were collected from hospital records, including demographic details, comorbidities, clinical presentation, laboratory findings, echocardiographic parameters, angiographic features, and in-hospital outcomes. Statistical analysis was performed using chi-square test and descriptive statistics, with a p-value <0.05 considered significant. Results: The mean age was 58.48±10.81 years, and 130(59.1%) were female. Hypertension was present in 100(45.5%), diabetes mellitus in 88(40.0%), and chronic kidney disease in 52(23.6%). Multivessel disease was observed in 116(52.7%) and cardiogenic shock in 34(15.5%). Mean left ventricular ejection fraction was 39.95±9.89%. Overall in-hospital mortality was 30(13.6%). Cardiogenic shock was significantly associated with mortality (χ²=4.66, p=0.031), as was chronic kidney disease (χ²=4.85, p=0.028). Diabetes mellitus (p=0.641), multivessel disease (p=0.192), and reduced LVEF (p=0.556) were not statistically significant predictors. Conclusion: In high-risk PCI patients, in-hospital mortality is primarily driven by cardiogenic shock and chronic kidney disease. Early identification of these factors is essential for risk stratification and improved clinical decision-making in acute coronary care settings. Keywords: Percutaneous Coronary Intervention, Myocardial Infarction, Cardiogenic Shock, Chronic Kidney Disease, In-hospital Mortality